Learning Media and Self-Efficacy: A Pathway to Science Literacy - Ridwan, Muhammad; Abdul Wahid, Sunar; Hidayati Pratiwi, Rina; Husin, Muhammad (Universitas Pendidikan Ganesha, 2025)
Scientific literacy is an essential 21st-century skill because it enables students to apply scientific knowledge in real-life contexts. However, in practice, the index of scientific literacy remains very low, as reflected in PISA data as well as observations in the field. This study aims to analyze the influence of students’ perceptions of learning media and self-efficacy on the scientific literacy skills of junior high school students in Batam, Indonesia. A total of 100 eighth-grade students from two public schools participated in this quantitative study. Data were collected using a validated Likert-scale questionnaire and a scientific literacy test, and were then analyzed using Pearson correlation and multiple linear regression. The results showed that perceptions of learning media were significantly correlated with scientific literacy (r = 0.372, p < 0.001), as was self-efficacy (r = 0.237, p = 0.018). However, only perceptions of learning media significantly predicted scientific literacy (β = 0.330, p = 0.001), whereas self-efficacy did not (β = 0.115, p = 0.258). The model explained 15% of the variance (R² = 0.150, F(2,97) = 8.541, p < 0.001). These findings highlight the importance of positive perceptions of learning media, particularly in terms of usefulness, interactivity, and emotional engagement. The implication is that teachers and curriculum developers need to design effective and engaging media to foster scientific literacy at the secondary school level.